Getting Evidence From Health Policy and Systems Research Into Policy and Practice for Controlling Endemic Tropical Diseases in Nigeria: Assessing Knowledge, Capacity, and Use - Ezenwaka, Uchenna; Onwujekwe, Obinna (Frontiers in Tropical Diseases, 2021)
Background Getting evidence from Health Policy and Systems Research (HPSR) into policy and practice for effective control of neglected tropical diseases (NTDs) is essential for providing better service delivery because evidence-informed decision-making improves the effectiveness of a health system and health outcomes. The paper provides new knowledge on the policy-/decision-makers’ level of knowledge, capacity to use, and how evidence from HPSR has been used in decision-making for the control of endemic tropical diseases (ETDs), especially the NTDs and malaria in Nigeria. Methods A cross-sectional qualitative study of decision-makers was undertaken in Anambra and Enugu states, southeast Nigeria. Data was collected through in-depth interviews (n=22) of purposively selected decision-makers to assess how HPSR evidence is translated into policy and practice for controlling ETDs. The respondents were selected based on their job description, roles, and involvement in the control of ETDs. Data were analyzed using the thematic content approach. Results There is a considerable level of knowledge on HPSR and its relationship with evidence-informed policy- and decision-making towards control of ETDs and health system strengthening. Organizational capacity to use HPSR evidence in decision-making was found to be weak due to various reasons such as no embedded structure for translating research evidence to policy and practice, lack of decision-making autonomy by individuals, and politically driven decisions. Few respondents have either ever used or are currently using HPRS evidence for developing/reviewing and implementing strategies for ETDs programs. Majority of the respondents reported that their main source of evidence was routine data from health information management system, which they found useful due to its representativeness and completeness. Main enabler for using HPSR evidence for decision-making is existing collaborations between researchers and policy-/decision-makers. Conclusion There is a high level of awareness about evidence from HPSR and the usefulness of such evidence in decision-making. However, this awareness does not translate to optimal use of evidence for decision-making due to weak organizational capacity and other constraints. There is the need to invest in capacity-building activities to develop a critical mass of users of evidence (policy-/decision-makers) to facilitate enhanced uptake of high-quality evidence into policy decisions for better control of ETDs.